2004
DOI: 10.1007/s11746-006-0942-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the autoxidation of TAG containing conjugated and nonconjugated C18 PUFA

Abstract: Four TAG containing linoleate (soybean-TAG), α-linoleate (perilla-TAG), conjugated linoleate (CLA-TAG), and conjugated linolenate (bitter gourd-TAG) were oxidized in the bulk phase at 50°C. The effects of α-tocopherol and Trolox (6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid) on the oxidation of these TAG were also studied. Progress of oxidation was determined by measuring the oxygen consumption, peroxide formation, and polymer formation. The rates of oxygen consumption and polymer formation of bitter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
5
22
0
Order By: Relevance
“…Furthermore, comparison of the increments of AnV and PC content which contains polymerized compounds revealed that the formation of PC content in secondary oxidation products occurred more rapidly in conjugated oils than in non-conjugated oils. The information described above corresponds quite well with the results of Suzuki et al 13) , which means that dimmer and polymer contents increased more rapidly with time in conjugated oil than in non-conjugated oil.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, comparison of the increments of AnV and PC content which contains polymerized compounds revealed that the formation of PC content in secondary oxidation products occurred more rapidly in conjugated oils than in non-conjugated oils. The information described above corresponds quite well with the results of Suzuki et al 13) , which means that dimmer and polymer contents increased more rapidly with time in conjugated oil than in non-conjugated oil.…”
supporting
confidence: 89%
“…To reconfirm the report by Suzuki et al 13) in non-aqueous autoxidation test, CLA-TAG, LA-TAG, CLN-TAG, and LN-TAG ( ) were incubated in a 30 thermostatic chamber for autoxidation in the dark and under fluorescent light irradiation at 960 lux. The hydroperoxide, carbonyl compound, and polar compound (PC), polymer contents were measured over time using potentiometric titration of the peroxide value (PV), colorimetric determination of anisidine value (AnV), TLC-FID and GPC analyses, respectively.…”
Section: Non-aqueous Autoxidation Testsupporting
confidence: 59%
See 1 more Smart Citation
“…Tsuzuki et al (2004) have, for example, reported that 9c,11t-CLA oxidizes at the same rate as linolenic acid (18:3; 9c,12c,15c) when monitored by substrate consumption, whereas when monitored by oxygen consumption it oxidizes at a similar rate to linoleic acid, and linolenic acid at a comparable rate to -eleostearic acid (18:3; 9c,11t,13t). Moreover, Van den Berg et al (1995) and Suzuki et al (2004) have demonstrated that peroxide value (PV) measurements produce incorrect results in kinetic studies when compared with result obtained by following substrate consumption.…”
Section: Figure 11mentioning
confidence: 99%
“…It is well established by PV and oxygen consumption measurements (Allen et al 1949), by MS (Muizebelt et al 2000), and by HPSEC (Luna et al 2007) that the autoxidation profile of CLA differs from that of its nonconjugated counterpart. Peroxide products accumulate more slowly and only in small amounts compared to linoleic acid (Allen et al 1949;Suzuki et al 2004). CLA absorb less oxygen per mole of oxidized substrate than linoleic acid (Allen et al 1949;Tsuzuki et al 2004) and produces mainly polymeric products (Luna et al 2007).…”
Section: Figure 11mentioning
confidence: 99%